Toxicity and Alpha Glucosidase Inhibitory Activity of Roasted Kedawung Seed (Parkia timoriana) - Supandi, Supandi; Hadi, Ismanurrahman; Arsul, Muhammad Ikhlas (Universitas Islam Negeri Alauddin Makassar, 2025)
Introduction: Kedawung (P. timoriana) seeds are empirically utilised as a traditional medicine; it also contains various phytochemical compounds, antioxidant activities as well as other beneficial pharmacological effects. In some regions in Indonesia, the utilisation of kedawung seeds is usually done by involving the roasting process. Aims: This study aims to investigate the effect of roasting on phytochemical compounds, toxicity and alpha glucosidase inhibitory effects. Method: Kedawung seeds were roasted at 150 ºC (15 minutes); then separated from the skin, powdered and macerated in ethanol. Result: The extract was phytochemically screened with the results obtained showing positive for saponins, flavonoids, alkaloids, and terpenoids. The following test is toxicity test using BSLT (Brine Shrimp Lethality Test) method as well as inhibitory activity on alpha glucosidase enzyme. The test results showed that kedawung extract had an LC50 of 78.18 ppm in the BSLT test, as well as inhibition of alpha glucosidase enzyme at 265.24 ppm. Conclusion: The results obtained show that the ethanol extract of roasted kedawung seeds still has phytochemical metabolite compounds, but is moderately toxic and has weak inhibition on alpha glucosidase